Cost-effectiveness of Gene Expression Classifier Testing of Indeterminate Thyroid Nodules Utilizing a Real Cohort Comparator. (October 2017) - Shapiro, Scott; Pharaon, Majed; Kellermeyer, Brian
Objective: To predict the cost-effectiveness of implementing routine gene expression classifier testing for thyroid nodules with indeterminate fine-needle aspiration cytology, by utilizing a real cohort of patients as a comparator. Study Design: Cost-effectiveness analysis of a retrospective cohort compared with a simulated cohort. Setting: Tertiary academic medical center. Subjects and Methods: We reviewed the records of all patients who underwent ultrasound-guided fine-needle aspiration from 2010 to 2014 at a tertiary academic medical center. All patients with Bethesda class III or IV cytopathology had the details of their management catalogued over the subsequent 2 years of care. These patients were assigned to the standard-of-care arm of the study. We compared the third-party payer costs of care and the proportion of patients who underwent surgery with a simulated cohort who underwent gene expression classifier testing after an initial indeterminate fine-needle aspiration (molecular test arm). Results: The cost of managing 1 nodule over 2 years was 2399 higher (range, 397-4399) for the molecular test group than the standard of care group. The molecular test group had a 13.1% decrease (base parameters; range, 0.73%-45.09%) in the number of patients undergoing surgery. Conclusion: When applied to a real cohort of patients, routine gene expression classifier is predicted to reduce the number of patients undergoing surgery but will increase cost of care. Cost-effectiveness is heavily dependent on prevalence of malignancy and gene expression classifier specificity.